Evaluation of the Impact of Educational Resource Management on Student Learning Outcomes - Marlina, Marlina; Mardiana, Ratna; Surbakti, Muliana; Pulungan, Lilik Hidayat (EDUCTUM: Journal Research, 2024)
Education is a conscious effort to help someone develop their potential systematically to achieve better self-quality. Educational institutions must continue to strive to improve the quality of education, not only in terms of physical facilities, but also the quality of educators. Educational management has an important role in training human resources to create superior and quality human resources, which will have a positive impact on national development. Internal and external factors affect student learning achievement, including psychological, sociological, physiological, skills, attitudes, social interactions, and family education factors. The method used in this study is the literature review system method (literature review). Literature review is usually interpreted as material that will be read in research related to a topic. Effective educational resource management has a significant impact on student learning outcomes. Research shows that good educational resource management, such as the availability and quality of educators, learning facilities, teaching materials, and other resources, contributes to improving student learning achievement, while lack of resources can hinder the learning process and low learning outcomes.